“DESIGN AND MANUFACTURING OF PROTECTION CAP FOR STUB SHAFT USING PLASTIC INJECTION MOULDING” - Malhar Mahajan; Atharva Joshi; Rohan Kshirsagar; Shrihari Khatri; Dr. Arun Thakare (International Journal of Innovations in Engineering Research and Technology, 2021)
In most industries, the product is manufactured at one place while assembled at another location. So, during transportation and handling, from manufacturing to assembly plant the part might get damaged, due to which it will not fit to assemble, leading to a big loss for the company. To avoid this, the part needs to be protected. By manufacturing of product using Plastic Injection Moulding (PIM), it will protect the part during transportation and handling. Considering strength as one of the important properties of the part, injection moulding is best suited for the mass production of plastic parts. Hence, injection moulding is most widely used in the local industries. This paper gives an insight into the Plastic Injection Moulding process from designing to manufacturing of the product, with certain process parameters that need to consider while designing for the selection of optimum material for the product.